Fat thickness as an alternative to marbling in beef carcass grading - Kenneth E. Kemp; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1981)
Data from 1669 steers show that equally palatable beef comes from carcasses with Choice marbling OR 0.4 inch of outside fat cover. Including cattle with 0.4 inch of fat and at least Slight marbling in a new choice grade would cut 20 to 30 days from the feeding period.
Keywords: Cattlemen& #x27; s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Fat thickness; Marbling; Carcass